The Efficacy and Safety of Treatment Outcomes for Refractory Benign Esophageal Strictures Using a Novel Combination of Needle-Knife Stricturoplasty, Balloon Dilation, and Steroid Injection (with Video) - Canakis,Andrew (2024)
Abstract Background and Aims: Benign esophageal strictures often present with dysphagia and can significantly impair a patient’s quality of life, especially when refractory to standard endoscopic techniques. When repeat dilations fail to achieve an adequate luminal diameter or resolve dysphagia, further therapy with needle-knife or steroid injections is needed. However, patients can still clinically fail. To manage such strictures, we employed a novel combination of all three techniques. Methods: Single-center case series of adult patients with benign strictures that were refractory to conventional endoscopic therapy and removable self-expanding metal stenting. Primary clinical success was defined as complete resolution in dysphagia. Secondary outcomes included periodic dilation index (frequency of dilations over the follow-up time), esophageal diameter changes, technical success, and complications. Results: Four patients (median age 49.7 years old, interquartile range [IQR] 30-59) underwent endoscopic therapy for complex, benign strictures using our triple therapy technique. Etiologies of the strictures included peptic strictures (n = 3) and an anastomotic stricture (n = 1). There was 100% technical success rate with no associated adverse events. There was a 50% clinical success rate, with 1 additional patient having partial improvement in dysphagia. The median diameter of the esophagus before and after triple therapy was 3.2 mm (IQR 3.5-5.5) and 12.8 mm (IQR 11.7-14.2), respectively. The periodic dilation index was 6.3 before and 1.5 after triple therapy. The median length of follow-up was 362.5 days. Conclusion: Triple combination therapy may be useful in benign strictures that are refractory to stan-dard techniques. Larger studies are needed to validate these findings.